Characterization of the anti‐HBV activity of HLP1–23, a human lactoferrin‐derived peptide. Issue 5 (18th March 2013) - Florian, Paula E.; Macovei, Alina; Lazar, Catalin; Milac, Adina L.; Sokolowska, Izabela; Darie, Costel C.; Evans, Robert W.; Roseanu, Anca; Branza‐Nichita, Norica
Abstract Lactoferrin (Lf) was shown to exhibit its antiviral activity at an early phase of viral infection and a mechanism whereby the protein interacts with host cell surface molecules has been suggested. In this study, human Lf (HLf) and seven HLf‐derived synthetic peptides (HLP) corresponding to the N‐terminal domain of the native protein (1–47 amino acids sequence) were assayed for their capacity to prevent hepatitis B virus (HBV) infection and replication using the HepaRG and HepG2.2.2.15 cell lines. Of the series tested, four peptides showed 40–75% inhibition of HBV infection in HepaRG cells, HLP1–23, containing the GRRRR cationic cluster, being the most potent. Interestingly, this cluster is one of the two glycosaminoglycan binding sites of the native HLf involved in its antiviral activity; however, the mechanism of the HLP1–23 action was different from that of the full‐length protein, the peptide inhibiting HBV infection when pre‐incubated with the virus, while no effect was observed on the target cells. It is suggested that the cationic cluster is sufficient for the peptide to interact stably with negatively charged residues on the virion envelope, while the absence of the second glycosaminoglycan binding site prevents its efficient attachment to the cells. In conclusion, this peptide may constitute a non‐toxic approach for potential clinical applications in inhibiting HBV entry by neutralizing the viral particles. J. Med. Virol. 85:780–788, 2013. © 2013 Wiley Periodicals, Inc.